2018
DOI: 10.1016/j.joule.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Heterojunctions of Graphene and 2D Perovskites Reveal Spontaneous Iodide Loss

Abstract: Using an ultrasensitive, exfoliated 2D perovskite single-crystal sheet/graphene heterostructure device, spontaneous iodide loss is revealed as an important degradation pathway of perovskites, which n-dopes perovskites by generating positively charged iodide vacancies. Furthermore, covering perovskites with graphene can suppress iodide loss, significantly improving perovskite stability. Our work not only provides important insights for future stable perovskite optoelectronic device development, but also demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 46 publications
2
45
0
Order By: Relevance
“…Various studies have shown that I 2 vapor can be released from both perovskite films and full solar cells under illumination. 37,39,41,68,69 For instance, using time-resolved mass spectrometry, Song et al 70 and Juarez-Perez et al 67 independently confirmed that I 2 vapor is one of the main volatile compounds when degrading perovskites at a temperature between 60 and 80 1C under illumination (the conditions used here).…”
Section: Energy and Environmental Science Papermentioning
confidence: 66%
“…Various studies have shown that I 2 vapor can be released from both perovskite films and full solar cells under illumination. 37,39,41,68,69 For instance, using time-resolved mass spectrometry, Song et al 70 and Juarez-Perez et al 67 independently confirmed that I 2 vapor is one of the main volatile compounds when degrading perovskites at a temperature between 60 and 80 1C under illumination (the conditions used here).…”
Section: Energy and Environmental Science Papermentioning
confidence: 66%
“…G, Optical image of an FET device based on (PEA) 2 PbI 4 . Reproduced with permission: Copyright 2018 Elsevier Inc 124 . H, Optical image of an FET device based on (PEA) 2 CsSn 2 I 7 .…”
Section: Methods Of 2d Perovskite Crystallizationmentioning
confidence: 99%
“… 109 Rand's group used graphene to cover 2D I‐containing perovskite single‐crystal (PEA) 2 PbI 4 to inhibit the spontaneous loss of iodine, reduce crystal degradation and improve the overall stability of the device (Figure 10G). 124 In addition to I‐based materials, there are also many Sn‐based perovskite FETs, such as phenylethyl ammonium tin iodide (PEA) 2 SnI 4 , and alkyl ammonium tin iodide (C n H 2n + 1 NH 3 ) 2 SnI 4 (n from 4 to 12) 127–132 . However, as Sn 2+ is easily oxidized to Sn 4+ in 2D perovskite, the environmental stability is worse than that of I‐based perovskite, so the single‐crystal devices are less reported 133 .…”
Section: Methods Of 2d Perovskite Crystallizationmentioning
confidence: 99%
“…The drawback of perovskite devices is that the device performance easily degrades in an ambient environment. The loss of iodide caused by chemical reactions between H 2 O and iodine‐containing species leads to performance degradation of perovskite devices . A commonly employed method to prevent this chemical degradation is to deposit an organic layer above the perovskite layer to obstruct the permeation of moisture.…”
Section: Electronic and Optoelectronic Applicationsmentioning
confidence: 99%